"You are not wrong about getting strong:" An insight into the impact of age group and level of competition on strength in Spanish football players - Soriano, M. A.; Paredes, V.; Comfort, P.; Jiménez-Ormeño, E.; Areces-Corcuera, F.; Giráldez-Costas, V.; Gallo-Salazar, C.; Alonso-Aubín, D. A.; Menchén-Rubio, M.; McMahon, J. J. (International Journal of Sports Physiology and Performance, 2024)
Objective This study aimed to compare the maximum and rapid force production of Spanish football players and explore the differences between age group and level of competition.